H Hubungan Tindakan Endoskopi Saluran Cerna Dengan Tingkat Kecemasan Pasien Di RSUD Kota Yogyakarta: The Relationship Between Gastrointestinal Endoscopy and Patient Anxiety Levels at Yogyakarta City Regional Hospital - Devianto, Aan; Afrida, Maryudella; Nurningsih, Nurningsih (Journal of Nursing Invention, 2024)
Background:Gastrointestinal endoscopy is a procedure to examine the internal organs of the gastrointestinal tract. This endoscopic procedure may cause anxiety. This anxiety can have negative consequences, such as increased pulse, breathing, blood pressure, lack of cooperation during the procedure, delay or cancellation of the procedure. Objective:Knowing the relationship between gastrointestinal endoscopy and patient anxiety level at Yogyakarta City Hospital. Method:This type of quantitative research with descriptive correlations design non probability sampling with accidental sampling technique, using univariate and bivariate data analysis and Spearman's Rho Test with a sample size of 54 respondents. The instruments used were the respondent characteristic data questionnaire and the Hamilton Anxiety Rating Scale (HARS) questionnaire. Result: The results of the Spearman's rho Nonparametric Correlations test obtained a value of r = 1.000, and p = 0.029 (p <0.05), there is a significant unidirectional and positive relationship between gastrointestinal endoscopy and patient anxiety levels. Conclusion: The age characteristics of the respondents were mostly 50-60 years old, female gender, high school education level, had private jobs, and the majority were Muslim. There is a significant relationship between gastrointestinal endoscopy and anxiety level, the relationship between the two variables is very strong and unidirectional because it is positive.